Web pembelajaran untuk meningkatkan pemahaman kalimat keterangan lampau bahasa Jepang - Apriliana Janatu Marwa; Suarna, Nana; Ali, Irfan; Efendi , Dendy Indriya (Universitas Islam Balitar, 2025)
Japanese, or Nihongo (日本語), is the primary language of Japan, spoken by more than 125 million people globally. It belongs to the Japonic language family and features a distinct writing system composed of Kanji, Hiragana, and Katakana. Kanji, derived from Chinese characters, while Hiragana and Katakana (referred to as Kana) are phonetic alphabets with 46 basic characters. Hiragana is used for native words and grammar, while Katakana is utilized for foreign words and emphasis. Japanese grammar follows a Subject-Object-Verb (SOV) structure, with social hierarchy reflected through the use of keigo, as well as past adverbial sentences and verb conjugations marked by formality. The global fascination with Japanese culture, including anime and manga, has sparked increased interest in the language. To facilitate learning, the author created a web-based learning platform using the Waterfall methodology, incorporating system engineering, requirement analysis, design, coding, testing, and maintenance phases. The platform is aimed at enhancing learners' understanding of past tense adverbial sentences, with pilot tests indicating considerable improvements in users' Japanese language abilities. Besides offering interactive content, the system also provides a well-organized and user-friendly learning experience. This study aims to positively impact Japanese language education and encourage broader adoption of educational technology, ultimately assisting learners in achieving higher Japanese proficiency in the digital age